THE HYPNOSIS AND THE POSTTRAUMATIC DISORDERS - Cardeña, Etzel; Maldonado, José; Galdón, María José; Spiegel, David (Anales de Psicología / Annals of Psychology, 1999)
The statistics show that the majority of us will experience at least one traumatic event during our lifetime, although only a minority will develop posttraumatic conditions (e.g., acute stress disorder or posttraumatic stress disorder). Hypnosis for the treatment of posttraumatic conditions has a long and venerable history. Its techniques should be particularly useful for these conditions because they seem to augment the efficacy of general therapeutic approaches, and because posttraumatic patients tend to be highly hypnotizable and suffer from dissociative and other symptoms amenable to hypnotic interventions. Hypnosis is well suited to a three phase approach for the treatment of posttraumatic conditions, with such techniques as relaxation, ego strengthening, and memory processing. Trauma therapists and theorists should consider serious training in hypnosis.